Effects of herbal medicine for dysmenorrhea treatment on accompanied acne vulgaris: a study protocol for a randomized controlled trial - Kwan-Il Kim; Hae Jeong Nam; Mia Kim; Junhee Lee; Kyuseok Kim (BMC, 2017)
Abstract Background The incidence of preadolescent acne among women is increasing. Acne deteriorates the quality of life; conventional treatment options are limited and have not been effective against acne, particularly acne associated with menstruation. Despite evidence that acne associated with menstruation abnormalities naturally improves when menstruation recovers to normal, there have only been few studies on the effects of dysmenorrhea treatment on acne. Therefore- we designed this study to assess the effects of gyejibokryung-hwan (GBH) and dangguijagyag-san (DJS), which are widely used in dysmenorrhea treatment, on acne associated with menstruation cycle. Methods This is a protocol for a randomized, double-blind, parallel-group, placebo-controlled and multicenter trial. One hundred and sixteen participants with dysmenorrhea accompanied by acne vulgaris will be recruited at three centers and randomized into two groups, the herbal treatment group and placebo group. The participants will receive GBH or DJS based on pattern identification or placebo granules thrice daily for 8 weeks, with an 8-week follow up. The primary outcome will be the mean percentage change in the count of inflammatory acne lesions. The secondary outcomes would be based on dysmenorrhea numeric rating scale, verbal multidimensional scoring system for dysmenorrhea, acne numeric rating scale, investigator's static global assessment scale of facial acne vulgaris, and safety testing. Adverse events will also be reported. Discussion The effects of GBH or DJS used in dysmenorrhea treatment on acne associated with the menstrual cycle will be evaluated. The findings of this trial will provide evidence regarding the effect of herbal medicine in improving acne vulgaris associated with menstruation in women. Trial registration Korean Clinical Trial Registry ( http://cris.nih.go.kr ; registration number: KCT0002259). Date of registration: March 10, 2017